2021
DOI: 10.3390/genes12081257
|View full text |Cite
|
Sign up to set email alerts
|

Wide Fontanels, Delayed Speech Development and Hoarse Voice as Useful Signs in the Diagnosis of KBG Syndrome: A Clinical Description of 23 Cases with Pathogenic Variants Involving the ANKRD11 Gene or Submicroscopic Chromosomal Rearrangements of 16q24.3

Abstract: KBG syndrome is a neurodevelopmental autosomal dominant disorder characterized by short stature, macrodontia, developmental delay, behavioral problems, speech delay and delayed closing of fontanels. Most patients with KBG syndrome are found to have a mutation in the ANKRD11 gene or a chromosomal rearrangement involving this gene. We hereby present clinical evaluations of 23 patients aged 4 months to 26 years manifesting clinical features of KBG syndrome. Mutation analysis in the patients was performed using pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…This variant was initially classified as a variant of uncertain significance as it had not been previously reported at the time of sequencing, but it is now being reclassified because of new information available: two additional patients carrying the exact same variant. The Arg2536Gln variant has been also recently reported in an unrelated patient affected with KBG syndrome, as a de novo event [13]. This patient has the following clinical features: poor weight gain, feeding problems and wide fontanel/delayed closure.…”
Section: Resultsmentioning
confidence: 83%
“…This variant was initially classified as a variant of uncertain significance as it had not been previously reported at the time of sequencing, but it is now being reclassified because of new information available: two additional patients carrying the exact same variant. The Arg2536Gln variant has been also recently reported in an unrelated patient affected with KBG syndrome, as a de novo event [13]. This patient has the following clinical features: poor weight gain, feeding problems and wide fontanel/delayed closure.…”
Section: Resultsmentioning
confidence: 83%
“…With the advent of the use of high-resolution CMA with specific NDD-enriched regions, several submicroscopic rearrangements in ANKRD11 are now emerging [ 23 ], as identified in PT12, who bears a 682 bp deletion. Most of the small deletions fall in non-coding regions of the gene, namely the first introns or the promoter region (CpG 205), suggesting their proneness to genomic rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…Given the molecular spectrum and broad phenotypic variability of KBGS, the optimal diagnostic approach is via multi-testing based on ANKRD11 sequencing—by single gene test or multi-gene panels—and chromosome microarray analysis (CMA) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could explain the high prevalence of ADHD in our sample compared to that from the 273 patients from the literature. Nevertheless, a recent study by Kutkowska-Kazmierczak and colleagues described that 86% of the 23 patients reported had "psychomotor hyperactivity" and proposed to include these symptoms in the diagnostic criteria of KBG syndrome [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical presentation of the syndrome is highly heterogeneous regarding both the phenotype and severity of the symptoms, with variable expressivity and penetrance [10]. This has resulted in a lack of a consensus clinical diagnostic criteria, with manifestations considered major and minor changing as new patients have been published [6][7][8][9][11][12][13].…”
Section: Introductionmentioning
confidence: 99%